ANÁLISE DISCRIMINANTE DAS CARACTERÍSTICAS GERENCIAIS ENTRE AS CONSTRUTORAS E PRESTADORAS DE SERVIÇOS DA CONSTRUÇÃO CIVIL - Lago, Monique Rau; Iarozinski Neto, Alfredo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study aims to analyze the management characteristics from builders and service provider companies in the construction industry. The information was gathered from both kinds of companies through surveys applied during 2016 and 2017, containing 5 groups of information: company profile, organizational characteristics, strategy and operation, performance and relationship with the customer and supplier. The paper reveals the main differences and similarities between the builders and service provider enterprises, according the obtained data.